PENGARUH KEPERCAYAAN ATASAN, LINGKUNGAN KERJA NON FISIK DAN REWARD TERHADAP KINERJA KARYAWAN (Studi pada PT Telekomunikasi Indonesia Tbk. Divisi Regional, Wilayah Jakarta Selatan) - Hernawan, Radityo Murti; Djastuti, Indi (Diponegoro Journal of Management, 2017)
Diminished performance from employee performance PT. Telekomunikasi Indonesia (persero) Tbk., area of south jakarta  in 2012 to 2013 to make the authors examine employee performance. This research is purposed to analyze the effects of Leader trust, non physical environment, and reward on employee’s performance. The phenomenon of fluctuation employee’s performance rate at PT. Telekomunikasi Indonesia (persero) Tbk., area of south jakarta indicate that the employee’s performance is not maximized. This study used three independent variables there are Leader trust, non physical environment, and reward. This study aims to examine and analyze the effects of Leader trust, non physical environment, and reward on employee’s performance at PT. Telekomunikasi Indonesia (persero) Tbk., regional division, area of south jakarta. Data collection methods used in this study are questionnaires using non random sampling method, the sample used in this study were permanent employees of PT. Telekomunikasi Indonesia (persero) Tbk., regional division, area of south Jakarta many as 93 respondents. This study uses data analysis methods include validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient determination test, F test and t test. The result showed that the variables of Leader trust, non physical environment, and reward affect positively on the employee’s performance of employees at PT. Telekomunikasi Indonesia (persero) Tbk., regional division, area of south Jakarta. These variables have an impact of 28,6% on employee’s performance. While the remaining 71.4% is influenced by other variables outside of this study